Propagation of Measurement-While-Drilling Mud Pulse during High Temperature Deep Well Drilling Operations. (29th April 2013) - Li, Hongtao; Meng, Yingfeng; Li, Gao; Wei, Na; Liu, Jiajie; Ma, Xiao; Duan, Mubai; Gu, Siman; Zhu, Kuanliang; Xu, Xiaofeng
Abstract : Signal attenuates while Measurement-While-Drilling (MWD) mud pulse is transmited in drill string during high temperature deep well drilling. In this work, an analytical model for the propagation of mud pulse was presented. The model consists of continuity, momentum, and state equations with analytical solutions based on the linear perturbation analysis. The model can predict the wave speed and attenuation coefficient of mud pulse. The calculated results were compared with the experimental data showing a good agreement. Effects of the angular frequency, static velocity, mud viscosity, and mud density behavior on speed and attenuation coefficients were included in this paper. Simulated results indicate that the effects of angular frequency, static velocity, and mud viscosity are important, and lower frequency, viscosity, and static velocity benefit the transmission of mud pulse. Influenced by density behavior, the speed and attenuation coefficients in drill string are seen to have different values with respect to well depth. For different circulation times, the profiles of speed and attenuation coefficients behave distinctly different especially in lower section. In general, the effects of variables above on speed are seen to be small in comparison.